Phases and Key Challenges in Indian Internet Startup Lifecycle: Transnational Entrepreneurship vs. Local Entrepreneurship - Krishna, H S; Bala Subrahmanya, M H (Technology Transfer and Entrepreneurship (Discontinued), 2016)
Of late, high-tech startups have been assuming increasing importance as a means of net employment generation, economic transformation and growth in the global economy. Among the emerging economies, India has been assuming increasing significance as a hub for high-tech startups, contributed among others by transnational entrepreneurs. Given this context, it is important to understand the key phases of the startup lifecycle and the corresponding challenges that entrepreneurs face in each of those phases. Once these challenges are understood, it is essential to understand the different ways in which entrepreneurs deal with these challenges and overcome them. With this background, this paper primarily examines the three important phases of high-tech startup lifecycle – emergence, survival and growth, in the context of transnational entrepreneurs as against local entrepreneurs, based on six case studies, two each for the three different phases. The case studies revealed the strategies adopted by the transnational entrepreneurs vis-à-vis local entrepreneurs with respect to market access, funding and role of Top Management Team (TMT) in the three different phases of startup lifecycle. Our findings indicate that if the local entrepreneur is as ‘resourceful’ as the transnational entrepreneur, the former need not lag behind and suffer relative to the latter, in dealing with the key challenges involved across the lifecycle of high-tech startups.
Keywords: Phases